Estudo da permeação de hidrogênio em reator com membrana de paládio: modelagem matemática e simulação computacional - Bernardes, Cristiane Junqueira (2009)
Hydrogen is the simplest and most common element in the universe. Currently, some industries use hydrogen to refine oil, and to produce ammonia and methanol. Since the combustion of hydrogen produces only water and energy, it is considered to be viable and environmentally safe. Most of the hydrogen produced in industrial scale is by the steam reforming process of methane. Since the reactions involved are strongly endothermic, due to thermodynamics restrictions, in order to obtain reasonable conversions it is necessary to use high temperatures in conventional reactors. The literature suggests the use of membrane reactors, due to membrane s permselective and products removal, the thermodynamic equilibrium is shifted, allowing higher conversions at lower operating temperatures. In order to better understand the steps involved in the permeation of hydrogen through the membrane, this work addresses the modeling of the membrane in each stage of permeation: external mass transfer, adsorption and desorption on the surface, transport to and from the bulk metal, and diffusion within the metal. The model was implemented and validated based on experimental data from literature. The model s results showed good agreement with other models implemented as well as experimental data. The model predicts which of the many steps of permeation is controlling the total hydrogen flux and it represents a useful tool to improve the flux prediction and to optimize the performance of separation systems in which palladium membrane is involved. The hydrogen flux predicted during the steam reforme of methane was used in a model of membrane reactor to asses the influence of steps in the permeation performance of the reactor, for the conversion of methane and the recovery of hydrogen. The reactor models considers the mass, energy and momentum equations. The model of the reactor that considers each stage of permeation to analyze the flux of hydrogen showed good agreement with the model of the reactor that follows Sievert s law to analyze the flux of hydrogen permeation, and with the experimental data. The model presented in this work showed a more smooth permeation flux along the reactor than the ones predicted by other models. In the equilibrium conditions the values of methane conversion and hydrogen recovery were similar to those predicted by a previous model from our group.